Cures for chance : adoptive relations in Shakespeare and Middleton - Ellerbeck, Erin (University of Toronto Press, 2022)
"Adoption allows families to modify, either overtly or covertly, what is considered to be the natural order. Cures for Chance explores how early modern English theatre questioned the inevitability of the biological family and proposed new models of familial structure, financial inheritance, and gendered familial authority. Because the practice of adoption circumvents sexual reproduction, its portrayal obliges audiences to reconsider ideas of nature and kinship. This study elucidates the ways in which adoptive familial relations were defined, described, and envisioned on stage, particularly in the works of Shakespeare and Middleton. In the plays in question, families and individual characters create, alter, and manage familial relations. Throughout Cures for Chance, adoption is considered in the broader socioeconomic and political climate of the period. Literary works and a wide range of other early modern texts--including treatises on horticulture and natural history and household and conduct manuals--are analysed in their historical and cultural contexts. Erin Ellerbeck argues that dramatic representations of adoption test conventional notions of family by rendering the family unit a social construction rather than a biological certainty, and that in doing so, they evoke the alteration of nature by human hands that was already pervasive at the time."--